Political economy and grand strategy [ a neoclassical realist view - Brawley, Mark R. [ (Mark Randal)] , 1960- (Routledge global security studies, 2010)
Examines traditional balance of power theory from a political-economic perspective, using historical examples, to draw out distinctions between the liberal and realist approach and how this affects grand strategy